Comparison of Autorefraction and Photorefraction with and without Cycloplegia Using 1% Tropicamide in Preschool Children - Ertuğrul Tan Yassa; Cihan Ünlü (Journal of Ophthalmology)
Purpose. We aimed to investigate whether the accuracy of the Plusoptix A09 photorefractor in children with ametropia is enhanced by cycloplegia with 1% tropicamide. Methods. A total of 70 eyes (70 children) were retrospectively reviewed. Noncycloplegic photorefraction, cycloplegia with 1% tropicamide, cycloplegic photorefraction, and cycloplegic refraction with a tabletop autorefractometer were performed on all subjects in this order. Measurements were compared statistically. Results. The mean age was 45.9 ± 11.4 months. The mean spherical equivalent (0.61 ± 1.03 diopters (D); range, −2.38 to 3.63 D) and mean spherical power (1.16 ± 0.92 D; range, −1.25 to 3.75 D) values that were acquired from the photorefraction without cycloplegia showed statistically significant differences from those of the autorefraction with cycloplegia (mean spherical equivalent = 1.00 ± 1.27 D; range, −1.50 to 4.25 D, mean spherical power = 1.60 ± 1.14; range, −1.25 to 4.50 D). The mean difference for the spherical equivalent was −0.39 ± 0.93 D (P=0.021; 95% limits of agreement (LoA) = −2.22 D to 1.44 D) and for spherical power was −0.44 ± 1.02 D (P=0.016; LoA = −2.44 D to 1.56 D). Without cycloplegia, Plusoptix A09 showed myopic shift, while after cycloplegia, it showed hyperopic shift. Spherical equivalent (mean difference (MD) ± SD = 0.78 ± 1.00 D, P<0.001; LoA = −1.17 D to 2.72 D) and spherical power (MD ± SD = 0.73 ± 1.04 D, P<0.001; LoA = −1.31 D to 2.77 D) values were significantly different from those of autorefraction with cycloplegia. Cylindrical power values obtained by photorefraction both with and without cycloplegia were not statistically different from those of autorefraction with cycloplegia (P>0.05). Conclusion. Cycloplegia with 1% tropicamide did not improve the accuracy of photorefraction using Plusoptix A09 in preschool children. The spherical equivalent and spherical power values obtained by photorefraction with cycloplegia were significantly higher from those obtained by autorefraction with cycloplegia.